Analisis Dampak kenaikan tarif PPN 12% Pada stabilitas keuangan keluarga karyawan sektor industri di Balikpapan - Mustari .; Anis Aulia Muslim; Delianti . (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
Value Added Tax (VAT) is a fiscal policy instrument that plays an important role in increasing government revenue. However, increases in the VAT rate also have the potential to exert pressure on household economic conditions. The implementation of a VAT rate increase to 12% has led to higher prices of goods and services, particularly daily consumption needs. This condition may affect purchasing power and household financial stability, especially among industrial sector employees in Balikpapan City, who generally have fixed incomes and household expenditure structures that are sensitive to price changes. This study aims to analyze the effect of the 12% VAT rate increase on the financial stability of households of industrial sector employees in Balikpapan City. The research employs a quantitative approach with descriptive and verificative research designs. The study population consists of 70 industrial sector employees in Balikpapan City, with a sample of 42 respondents selected using the Slovin formula and a random sampling technique. Data were collected through Likert-scale questionnaires, observations, interviews, and literature reviews. The data sources comprise primary and secondary data. Data analysis was conducted using SPSS software through validity tests, reliability tests, classical assumption tests, simple linear regression analysis, t-tests, and coefficient of determination analysis.The results indicate that the 12% VAT rate increase has a negative and significant effect on the financial stability of households of industrial sector employees. The majority of respondents experienced an increase in monthly household expenditures following the implementation of the policy, resulting in a decline in household budget management capacity. The increase in the VAT rate to 12% is proven to reduce household financial stability among industrial sector employees. These findings emphasize the importance of considering microeconomic impacts in the formulation of fiscal policy to ensure that efforts to increase government revenue do not impose excessive pressure on the welfare of fixed-income households.